GSM based patient heart beat monitoring system / Muhammad Shafique Nazli, Abdul Afidz Abdul Aziz and Nur Yasmine Abdul Samat - Nazli, Muhammad Shafique; Abdul Aziz, Abdul Afidz; Abdul Samat, Nur Yasmine (2015)
There is a vast growth of VLSI technology and Global System for Mobile communication, (GSM) communication in these days. This project deals about the implementation of GSM technology in Medical applications. This wireless communication would not only provide them with safe and accurate monitoring, but also fast response. In this project, heartbeat of patient are measured by using pulse sensors as analog data, later it is converted into digital data using ADC, which is suitable for wireless transmission using paging messages through a GSM modem. The ATmega328 micro controller IC in aduino is used for temporary storage of the data used for transmission.